Molecular Profile and the Effectiveness of Antimicrobials Drugs Against Staphylococcus aureus and Pseudomonas aeruginosa in the Diagnostic Approaches of Otitis Infection - Almuhayawi MS; Gattan HS; Alruhaili MH; Alharbi MT; Nagshabandi MK; Tarabulsi MK; Almuhayawi SM; Al Jaouni SK; Selim S; Alanazi A; Alruwaili Y; Faried OA; et al. (Infection and Drug Resistance, 2023)
Mohammed S Almuhayawi,1 Hattan S Gattan,2,3 Mohammed H Alruhaili,1,3 Mohanned Talal Alharbi,4 Mohammed K Nagshabandi,4 Muyassar K Tarabulsi,4 Saad M Almuhayawi,5 Soad K Al Jaouni,6 Samy Selim,7 Awadh Alanazi,7 Yasir Alruwaili,7 Osama Ahmed Faried,8 Islam Amin,9 Mohamed E Elnosary10 1Department of Clinical Microbiology and Immunology, Faculty of Medicine, King AbdulAziz University, Jeddah, 21589, Saudi Arabia; 2Department of Medical Laboratory Technology, Faculty of Applied Medical Sciences, King Abdulaziz University, Jeddah, 21589, Saudi Arabia; 3Special Infectious Agents Unit, King Fahad Medical Research Center, King AbdulAziz University, Jeddah, 21589, Saudi Arabia; 4Department of Medical Microbiology and Parasitology, Faculty of Medicine, University of Jeddah, Jeddah, 23218, Saudi Arabia; 5Department of Otolaryngology-Head and Neck Surgery, Faculty of Medicine, King Abdulaziz University, Jeddah, Saudi Arabia; 6Department of Hematology/Oncology, Yousef Abdulatif Jameel Scientific Chair of Prophetic Medicine Application, Faculty of Medicine, King Abdulaziz University, Jeddah, 21589, Saudi Arabia; 7Department of Clinical Laboratory Sciences, College of Applied Medical Sciences, Jouf University, Sakaka, 72341, Saudi Arabia; 8Medical Microbiology and Immunology Department, Faculty of Medicine, Beni-Suef University, Beni-Suef, 62513, Egypt; 9Central Laboratory, Ismailia General Hospital, Ismailia, Egypt; 10Botany and Microbiology Department, Faculty of Science, Al-Azhar University, Nasr City, Cairo, 11884, EgyptCorrespondence: Mohammed S Almuhayawi; Samy Selim, Email msalmuhayawi@kau.edu.sa; sabdulsalam@ju.edu.saBackground: Otitis externa and otitis media are two types of ear infections that affect people of all ages, although they are more common in newborns and young children. Antibiotic usage, healthcare, and advanced age all play a role in the development of this illness.Methods: Fifty-eight patients with various kinds of infections of the ears were voluntary patients attending the outpatient clinics of the Prince Mutaib Bin Abdulaziz Hospital in Sakaka, Al Jouf, Saudi Arabia, examined to evaluate the role of bacteria and the likely significance of plasmids in their antibiotic resistance as ear infectious agents.Results: Staphylococcus aureus and Pseudomonas aeruginosa are the most prevalent bacteria found in ear infections. The greatest number of major bacterial isolates were S. aureus (54%), followed by P. aeruginosa (13%), whereas a smaller number of isolates (3%) were from Streptococcus pyogenes, Bacillus subtilis, and Proteus vulgaris, respectively. Mixed growth was noted in 3.4% of instances. The isolation rate for Gram-positive organisms was 72%, while the rate for Gram-negative species was 28%. All the isolates had DNA greater than 14 kilobases. Hind III analysis of the plasmid DNA extracted from the resistant strains of ear infection demonstrated that antibiotic-resistance plasmids were extensively dispersed. Exotoxin A PCR amplification indicated 396 pb PCR-positive DNA for all identified samples, with the exception of three strains for which no band was observed. Patients in the epidemiological study ranged in number, but all were linked together for the purposes of the study because of their shared epidemiological characteristics.Conclusion: Vancomycin, linezolid, tigecycline, rifampin, and daptomycin are all antibiotics that have been shown to be effective against S. aureus and P. aeruginosa. Microbiological pattern evaluation and antibiotic sensitivity patterns of the microorganisms providing empirical antibiotics are becoming increasingly crucial to minimize issues and the development of antibiotic-resistant strains.Keywords: bacterial ear infections, otitis externa, otitis media, Staphylococcus aureus, Pseudomonas aeruginosa, exotoxin A, plasmid, antibiotic resistance, Saudi Arabia